Opportunities and challenges of using generative AI to personalize educational assessment - Arslan, Burcu; Lehman, Blair; Tenison, Caitlin; Sparks, Jesse R.; López, Alexis A.; Gu, Lin; Zapata-Rivera, Diego (Frontiers in Artificial Intelligence, 2024)
In line with the positive effects of personalized learning, personalized assessments are expected to maximize learner motivation and engagement, allowing learners to show what they truly know and can do. Considering the advances in Generative Artificial Intelligence (GenAI), in this perspective article, we elaborate on the opportunities of integrating GenAI into personalized educational assessments to maximize learner engagement, performance, and access. We also draw attention to the challenges of integrating GenAI into personalized educational assessments regarding its potential risks to the assessment’s core values of validity, reliability, and fairness. Finally, we discuss possible solutions and future directions.